Structural characterisation of MBE grown zinc-blende Ga1-xMnxN/GaAs(001) as a function of Ga flux - Han, Y.; Fay, Mike W.; Brown, Paul D.; Novikov, Sergei V.; Edmonds, K.W.; Gallagher, B.L.; Campion, R.P.; Foxon, C.T. (Springer-Verlag, 2005)
Ga1-xMnxN films grown on semi-insulating GaAs(001) substrates at 680°C with fixed Mn flux and varied Ga flux demonstrated a transition from zinc-blende/wurtzite mixed phase growth for low Ga flux (N-rich conditions) to zinc-blende single phase growth with surface Ga droplets for high Ga flux (Ga-rich conditions). N-rich conditions were found favourable for Mn incorporation in GaN lattice. α-MnAs inclusions were identified extending into the GaAs buffer layer.